2005
DOI: 10.1038/sj.npp.1300796
|View full text |Cite
|
Sign up to set email alerts
|

Amoxapine as an Atypical Antipsychotic: A Comparative Study Vs Risperidone

Abstract: Amoxapine is marketed as an antidepressant. However, its invitro profile, receptor occupancy and preclinical effects are very similar to atypical antipsychotics. Amoxapine has also shown efficacy as an atypical antipsychotic in open trials. The objective of this study was to compare the antipsychotic and side effect profile of amoxapine and risperidone in a randomised assignment, standardized dosing, doubleblind trial of acutely psychotic patients with schizophrenia. A total of 48 schizophrenic patients were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…For some AP, only 1 study was available, or data could not be used (sd or se could not be calculated) – these were therefore not included in the meta-analyses. The excluded AP and their weight change are amoxapine 1.05 kg (<6 wk, n = 22) [42], blonanserine 1.29 kg, sd = 3.48 (6–16 wk, n = 92) [43], fluphenazine −2.6 (16–38 wk, n = 9) [44], iloperidone 2.6, sd = 3.7 (<6 wk, n = 1239) [45], levomepromazine 4.1 (16–38 wk, n = 19) [46], lurasidone 0.9 kg (<6 wk, n = 90) [47], pimozide 2.9 (6–16 wk, n = 24) [48] and zuclopentixol 0.6 (6–16 wk, n = 19) [49]. The I-square of the included studies varied strongly, ranging from 10.3%–99.8% (in case 4 or more studies were included in the analysis), indicating little heterogeneity to very strong heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…For some AP, only 1 study was available, or data could not be used (sd or se could not be calculated) – these were therefore not included in the meta-analyses. The excluded AP and their weight change are amoxapine 1.05 kg (<6 wk, n = 22) [42], blonanserine 1.29 kg, sd = 3.48 (6–16 wk, n = 92) [43], fluphenazine −2.6 (16–38 wk, n = 9) [44], iloperidone 2.6, sd = 3.7 (<6 wk, n = 1239) [45], levomepromazine 4.1 (16–38 wk, n = 19) [46], lurasidone 0.9 kg (<6 wk, n = 90) [47], pimozide 2.9 (6–16 wk, n = 24) [48] and zuclopentixol 0.6 (6–16 wk, n = 19) [49]. The I-square of the included studies varied strongly, ranging from 10.3%–99.8% (in case 4 or more studies were included in the analysis), indicating little heterogeneity to very strong heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…Amoxapine is an antidepressant with a receptor profile similar to that of neuroleptics (Anton et al ., 1983; Apiquian et al ., 2005). It increased prolactin levels significantly more than desipramine (Anton et al ., 1983).…”
Section: Antidepressantsmentioning
confidence: 99%
“…It increased prolactin levels significantly more than desipramine (Anton et al ., 1983). In a comparison study of 39 patients with risperidone, amoxapine was found to have lower incidence of EPS and less prolactin elevation (Apiquian et al ., 2005).…”
Section: Antidepressantsmentioning
confidence: 99%
“…In systematic doubleblind trials, amoxapine was found to be of equal efficacy to that of an antidepressant and an antipsychotic (Anton and Burch, 1990). A recent study found that the antipsychotic activity of amoxapine was comparable with that of risperidone (Apiquian et al, 2005). Furthermore, because amoxapine is now off-patent and can be produced at generic prices, the drug could potentially rival other typical antipsychotics.…”
mentioning
confidence: 98%
“…Because amoxapine is a relatively weak reuptake inhibitor, it was suggested that the molecule may have the properties of an atypical antipsychotic agent (Apiquian et al, 2005). The upper range of therapeutic plasma concentrations of amoxapine has been reported from 0.2 to 0.4 g/ml (0.637-1.912 M) in human body (Winek et al, 2001).…”
Section: Amoxapine Inhibited I K 443mentioning
confidence: 99%